Inventory System for Physiotherapy Laboratory Facilities Based on a Website - Amalia, Farah Rizki; Pristianto, Arif; Naufal, Adnan Faris; Susilo, Taufik Eko; Bagassabirin, Nugrah Satria; Putri, Rafika Sakina (Gaster, 2024)
Background: Touching the digital era requires innovation to make work easier, including the inventory system so that it is more optimal, effective and efficient. The aim of this research is to facilitate the inventory process of laboratory equipment so that it is more optimal, effective and efficient. Methods: This research applies the Research and Development (RnD) method. The website prototype was assessed by two experts who have high qualifications, including master's degrees and experience in creating physiotherapy service applications. Apart from assessment by experts, the prototype was also evaluated by physiotherapy students from Muhammadiyah University of Surakarta class 2021 to 2023 via an online questionnaire. Results: Test results show that the existing features and menus provide ease of use in providing information to users. Based on the results of expert assessments and testing of the website, it was found that the website can be used according to its function, although there are still many shortcomings and things that need to be improved to be used as a reference for further research and development. Conclusion: The website in the form of a prototype laboratory facility inventory system implemented in the UMS physiotherapy study program is quite suitable for use, although it still requires further improvement and development so that the website is better to use.